Teknik Jahit Bulu Mata pada Mata Asimetris untuk Tata Rias Pengantin Adat Minang - Putri, Aldila; Maspiyah; Arita Puspitorini; Dindy Sinta Megasari (Journal of Beauty and Cosmetology (JBC), 2022)
This study aims to 1) find out the technique of sewing eyelashes on asymmetric eyes for Minang traditional bridal makeup, and 2) find out the results of make-up using eyelash sewing techniques on asymmetric eyes for Minang traditional bridal makeup. This research method uses quantitative descriptive with a quasi-experimental research design with a one shoot case study approach. The research instrument used was observation with a total of 30 observers including 6 expert panelists and 24 trained panelists. The results of this study were obtained, including the application of eyelash sewing techniques to asymmetric eyes reaching 100%. The results of the application of the eyelash sewing technique on asymmetric eyes for Minang traditional bridal make up got the following scores: Neatness of eyelash sewing technique with a score of 3.76, Smoothness of eye makeup with a score of 3.83, Symmetry of eye makeup with a score of 3.4 The overall makeup compatibility with a score of 3.63 and the suitability of eye makeup with the choice of clothing colors with a score of 3.83.Keywords: Eyelash Sewing Technique, Asymmetric Eyes, Minang Traditional Bride